2015
DOI: 10.1001/jamadermatol.2015.0384
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline for Recurrent and/or Chronic Erythema Nodosum Leprosum

Abstract: the medical record but was not standardized, the follow-up criterion of interest was "general improvement" in erythromelalgia without obtaining further details, and many patients were using other medications. Nonetheless, these results suggest that a topical preparation of midodrine, 0.2%, is well tolerated and improves symptoms of erythromelalgia. Further investigation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…While thalidomide is highly teratogenic (with a propensity to produce birth defects if taken during pregnancy) and produces adverse effects like peripheral neuropathy, clofazimine is associated with troublesome skin pigmentation and gastrointestinal side‐effects. Although minocycline has been used in small studies, the drug itself has been reported to precipitate ENL in patients with leprosy by killing Mycobacterium leprae organisms, in addition to causing cutaneous pigmentation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While thalidomide is highly teratogenic (with a propensity to produce birth defects if taken during pregnancy) and produces adverse effects like peripheral neuropathy, clofazimine is associated with troublesome skin pigmentation and gastrointestinal side‐effects. Although minocycline has been used in small studies, the drug itself has been reported to precipitate ENL in patients with leprosy by killing Mycobacterium leprae organisms, in addition to causing cutaneous pigmentation …”
Section: Discussionmentioning
confidence: 99%
“…Although minocycline has been used in small studies, the drug itself has been reported to precipitate ENL in patients with leprosy by killing Mycobacterium leprae organisms, in addition to causing cutaneous pigmentation. 8 Apremilast is a U.S. Food and Drug Administration-approved drug used clinically in the management of chronic plaque psoriasis and psoriatic arthropathy. By selective PDE-4 inhibition, it increases intracellular cyclic adenosine monophosphate levels and downregulates multiple inflammatory mediators involved in T helper cell 1 and T helper cell 17 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two additional cases of E . pasteuriana were reported from Guangzhou, China, in a renal transplant recipient [ 23 ] and in a patient treated with high-dose corticosteroids [ 24 ].…”
Section: A Leap From Obscurity To Global Medical Importancementioning
confidence: 99%
“…17,18 The addition of minocycline to MDT has been shown to be more efficacious than the MDT alone 9 and has been found to impart a better control of reactional episodes. 19,20 There is a dearth of studies assessing the effectiveness of alternative/newer regimens in the management of leprosy in the last few decades. In a prospective study on 21 MB patients using the same alternative regimen as used in the present study, Maia et al 21 found that all patients tolerated the drugs well, with satisfactory compliance, and no events adverse enough to warrant discontinuation of the treatment were noted.…”
Section: Discussionmentioning
confidence: 99%